No embalo da rede: o impacto produzido pelo cuidado na vida dos idosos de Bagé, que frequntam o Centro do Idoso - Caetano, Silvana Kinczel (2011)
This paper presents the conclusions of the research about the work done by the professional team responsible for the Elderly Center of Bagé, RS, through the observation of this proposal starting from the point of view of the user population, of the elderly relatives that attend the Elderly Center and of the professionals that attend them and develop the planned activities. The original project of this Center is based on the necessity of sociability, health promotion, spirituality, learning and citizenship, presumptuously necessary and which are stimulating of an active aging. The impact produced by the care, from the creation of the Elderly Center, in the life of the user population as a concrete space of applying public politics that consists the social net of municipality of Bagé, that‟s what we intend to measure here. This way, we believe that the research and the conclusion of the real reach of the practices that it offers, being a relevant knot of the attention net and dedicated to the attendance and care of a population that exceeds 12% of the population of Bagé, it will stimulate the reflection and it will enhance the changes that still need to be implemented in search of a better life quality of this segment, strengthening the feeling of membership of the citizens to their community.